Pengaruh Kesadaran Wajib Pajak, Kepatuhan Wajib Pajak, Penagihan Pajak, dan Pemeriksaan Pajak Terhadap Penerimaan Pajak - Ischabita, Nafisa; Hardiwinoto, Hardiwinoto; Nurcahyono, Nurcahyono (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2022)
This study aims to determine the effect of taxpayer awareness, taxpayer compliance, tax collection, and tax audit on tax revenue. The population of this study is an individual taxpayer registered at the KPP Pratama Semarang Timur with 100 respondents. The sampling technique used is Convenience Sampling or determining the sample based on convenience. Data was collected by distributing questionnaires. Data were analyzed using multiple linear regression analysis. The results of this study are that taxpayer awareness, tax collection and tax audit variables have a significant effect on tax revenue, while taxpayer compliance has no significant effect on tax revenue